Vernacularizing Bulūgh al-Marām in Buton: An Intertextual Study of Sabīl al-Salām - Naomi, Putri; Muhammad Fatkhi, Rifqi; Azhari, Alhamra; Rohmat Yanuri, Yusuf (Jurnal Ilmiah Al-Mu'ashirah: Media Kajian Al-Qur'an dan Al-Hadits Multi Perspektif, 2026)
The Buton Sultanate in the 19th century CE was at the peak of its intellectual golden age, driven by the dual role of Sultan Muḥammad ‘Aidrūs as both a political ruler and an ulamā actively shaping the local intellectual tradition. This article examines his contribution to Hadith transmission in the Nusantara by examining the intertextual relationship between the Sabīl al-Salām manuscript by ‘Aidrūs and the book Bulūgh al-Marām by Ibn Ḥajar. This study employs a library research method, using primary sources a manuscript copy of Sabīl al-Salām from the British Library collection (EAP212/2/17) and the text of Bulūgh al-Marām. The data analysis technique applies Julia Kristeva’s intertextuality approach to trace textual transformations. The results of the study reveal the presence of four intertextual principles: (1) haplology (textual simplification by omitting explanations of the chains of transmission or sanad for the readers' practicality); (2) expansion (broadening the scope of chapter titles to be more holistic); (3) modification (adjusting the Hadith content to more prominently highlight the virtues of deeds in accordance with the sociological needs of the Butonese society); and (4) parallelism (similarities in the reference hierarchy of the primary authoritative Hadith books). Additionally, the level of accuracy of the Hadith quotations by ‘Aidrūs proves to be remarkably high, indicated by the high precision of the text (matan) redaction's conformity with the original reference Hadith books, leaving only a few minor discrepancies. In conclusion, this manuscript proves that the adaptation of global texts in the Nusantara represents an effort of vernacularization that enriches local Islamic literature.